Revitalising Development Administration for Environmental Disaster Risk Reduction in Gorontalo - Djafar, Franky (Jurnal Administrasi Publik (Public Administration Journal), 2025)
This study examines the factors influencing the effectiveness of disaster mitigation policies in Gorontalo and explores how revitalizing development administration can enhance these efforts. The research is grounded in the context of weak inter-agency coordination and limited community participation, which pose significant challenges to policy implementation. Data were collected through literature review, in-depth interviews, focus group discussions (FGD), and document analysis. The findings reveal that effective inter-agency coordination, human resource capacity, and community engagement are critical to successful disaster risk mitigation. Furthermore, integrating sustainable development principles and empowering local communities are essential to strengthening resilience. The study concludes that improving governance structures, fostering institutional synergy, and promoting active community involvement are necessary steps to enhance the effectiveness of disaster mitigation policies in Gorontalo and other disaster-prone regions.